Modern discussions on the Objectives of Sharia in the Present Era: Perspectives and Methods: عصرِحاضر میں مقاصدِشریعت کے جدید مباحث: تناظر اور مناہج - Qaisar, Dr. Zuha (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Maqasid al-Shariah is a subject which is very old but its debats is heard more in modern times. In this regard, the majority of scholars carry out modern ijtihads in connection with the tradition, and with the help of this term, an attempt is being made to create such an unauthorized breadth in jurisprudence which weakens the connection with the texts and the Shariah injunctions in the cultural confusion. A lot of work has already been done on Maqasid al-Shariah in general, both historically and analytically. This article aims to reflext on contemporary methods of Maqasid because, there is no such work in a systematic way in which the cultural aspect of the objectives and its methodology and effects have been discussed.